2022
DOI: 10.3390/ijerph19020983
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Occupational Stress, Change in Work Environment during the COVID-19 Pandemic, and Depressive and Anxiety Symptoms among Non-Healthcare Workers in Japan: A Cross-Sectional Study

Abstract: This study aims to clarify the effect of occupational stress and changes in the work environment on non-healthcare workers’ (HCWs) mental health during the third wave of the COVID-19 pandemic in Japan. A web-based, cross-sectional survey was conducted from 16 to 17 December 2020. Data from 807 non-HCWs were included. We evaluated occupational stress using the Generic Job Stress Questionnaire (GJSQ). Depressive and anxiety symptoms were assessed using the Japanese version of the Patient Health Questionnaire-9 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 56 publications
3
14
0
3
Order By: Relevance
“…Levels of depression have increased due to the pandemic and subsequently decreased slightly in 2022. Because, the present study showed that levels of depressive symptoms in January 2022 were lower than in 2020 and 2021, and these scores in January 2022 were nearly the same as scores obtained before the pandemic [29,30] rather than during the pandemic [14]. The same result was found for the number of suicides in Japan [13].…”
Section: Changes Levels Of Depressive and Ptsd Symptomssupporting
confidence: 82%
See 1 more Smart Citation
“…Levels of depression have increased due to the pandemic and subsequently decreased slightly in 2022. Because, the present study showed that levels of depressive symptoms in January 2022 were lower than in 2020 and 2021, and these scores in January 2022 were nearly the same as scores obtained before the pandemic [29,30] rather than during the pandemic [14]. The same result was found for the number of suicides in Japan [13].…”
Section: Changes Levels Of Depressive and Ptsd Symptomssupporting
confidence: 82%
“…In Japan, mild lockdowns have been implemented intermittently, because the pandemic has exhibited a repeated pattern of expansion and a contraction. The rate of suicides in Japan increased from July 2020 to June 2021 [13], and previous research has reported that mental health among Japanese people decreased during the early stages of the pandemic [14,15] and at the beginning of 2021 [16].…”
Section: Introductionmentioning
confidence: 99%
“…One study suggests that the shift to remote work at home due to the covid-19 pandemic generated a greater influence on mental health, mainly due to increased workload and overtime [ 37 ]. Another study demonstrated relationships between drastic changes in work style, workplace, economic deterioration, feelings of job insecurity with anxiety symptoms [ 38 ]. In line with the WHO survey (2017), in which younger individuals had a higher prevalence of anxiety disorder, with a decline after 49 years old [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Japan, strict lockdowns have never been implemented, but mild lockdowns have been implemented intermittently because the pandemic has exhibited a repeated pattern of expansion and contraction. Previous research conducted in 2020 and 2021 reported that the prevalences of depressive symptoms in Japan were 18.35% and 43.4%, respectively, and the rate might have increased before the pandemic [ 23 25 ]. Additionally, the rate of suicide in 2020 increased by 4.5% compared to that in 2019 [ 26 ].…”
Section: Introductionmentioning
confidence: 99%